Design of heterogeneous catalysts for selective hydrogenation of cinnamaldehyde and asymmetric hydrogenation of dimethyl itaconate - Zhen, Guo (2011)
As one of the most important industrial processes, catalytic hydrogenation, including both symmetric and asymmetric hydrogenation have found numerous applications in essential areas, such as energy production, agriculture, pharmaceutical, commodity chemicals and environment protection. In general, heterogeneous catalysts are more preferable than homogeneous catalysts due to their recyclability and a wide range of applicable reaction conditions. In addition to the catalytic activity, the selectivity of a hydrogenation catalyst becomes increasingly significant, particularly in fine chemical synthesis industry. In this PhD work, two model hydrogenation reactions—chemo-selective hydrogenation of cinnamaldehyde and asymmetric hydrogenation of dimethyl itaconate were tackled, aiming to find superior heterogeneous hydrogenation catalysts based on the results of many pioneer works. We attempted to contribute new understandings and concepts on the design of hydrogenation catalysts mainly in terms of the strategies of catalyst preparation, physicochemical characteristics of active sites, surface chemistry of supports and specific interactions between the active sites and supports.